PEREMPUAN DALAM PERSPEKTIF HUKUM PIDANA - Zaidan, M Ali (Jurnal Yuridis, 2014)
Women by nature are vulnerable. Therefore, the law should treat these group in a fair menner, namely by providing maximum protection on their interest. Criminal law provides protection from a high criminal threat against those who comitted violence against women particularly in the domestic sphere. The movement of women who ar trying to elevate women is one way that must be accomodated bay setting strict laws and definite. Any violation of womens rights is essentially a violation of human rights.